FLOATING MULTIPLE UNIT MINITABLETS OF METOPROLOL SUCCINATE: FORMULATION, IN VITRO AND IN VIVO CHARACTERIZATION - PANDA, MADHULITA; RAO, M. E. BHANOJI; PANDA, JNYANARANJAN; PATRA, C. H. NIRANJAN; PATRO, GANESH (International Journal of Applied Pharmaceutics, 2021)
Objective: In this present research, formulation of floating multiple unit minitablets of metoprolol succinate without using gas generating agent was attempted with an objective of increased residence time, sustained release, and improved oral bioavailability. Methods: Solid dispersions were prepared with lipophilic carriers such as compritol ATO888, Gelucire 43/01, Gelucire 39/01, and precirol ATO 05 was formulated using fusion technique. Neusillin US2 was used as an adsorbent. The solid dispersions were compressed into minitablets, weighing 20 mg, and then filled into ‘0’ size capsule. Results: Formulation F9, F10, F14, and F15 showed instantaneous floating lag time, i.e., 0 min, floating time more than 12 h, and sustained release up to 12 h. Pharmacokinetic study of the optimized formulation (F9) showed 2.46 times increase in area under the curve with increased residence time. Conclusion: Hence gelucire 43/01 based floating multiple unit minitablets of metoprolol succinate can be considered a promising approach.